Representation of Terrorism in 22 July Movie (John Fiske Semiotic Analysis) - Luthfi Fathullah; Indah Wenerda (Publikasi Indonesia, 2024)
Paul Greengrass' 22 July depicts the tragic events of the July 22, 2011 terrorist attack in Norway. This research aims to describe the representation of terrorism in the movie